Compendium of Philippine environment statistics, 2006. - Philippines. National Statistical Coordination Board (Makati City National Statistical Coordination Board, 2006)
Covers data of flora and fauna, atmosphere, water, land and soil, mineral and energy, and human settlements in Philippines.
Keywords: Natural resources -- Philippines -- Statistics; Environmental auditing -- Philippines; Natural resources surveys -- Philippines; Environmental impact analysis -- Philippines; Philippines -- Environmental conditions -- Statistics -- Periodicals